Pengolahan Tekanan Tinggi Terhadap Evaluasi Mikrobiologi, Fisikokimia dan Sensori Minuman Ekstrak Tebu (Saccharum officinarum Linn) - Hasibuan, Diajeng Nur Syahfitri; Siregar, Muhammad Said; Mokhtar, Tun Norbrillinda; Arshad, Mohamad Helmi Mohd; Mohamad, Nur Ilida; Lazim, Mohd Izwan Mohd (Politeknik ATI Padang, 2025)
Sugarcane extract (Saccharum officinarum Linn) is a natural beverage rich in sucrose, glucose, and fructose, making it sweet and refreshing. However, its high sugar content, combined with high water activity and the absence of natural preservatives, makes it highly perishable. These conditions create an ideal environment for microbial growth, leading to enzymatic browning, fermentation, and contamination by spoilage microorganisms, significantly reducing its shelf life. To extend its shelf life while maintaining quality, effective preservation methods are essential. This research evaluates High Pressure Processing (HPP) as a non-thermal preservation technique, comparing untreated sugarcane extract (T1) with HPP-treated extracts at 400 MPa for 10 minutes (THPPc) and at lower pressures (200 MPa and 300 MPa). Analyses included Total Plate Count (TPC), yeast and mold (Y&M) counts, total coliforms, Escherichia coli, and physicochemical properties such as viscosity, water activity, brix, moisture, and color. Results indicated that HPP significantly reduced TPC from 2.60 × 10⁴ CFU/mL in untreated extract to 1.39 × 10² CFU/mL in THPPc. The Y&M count in the HPP-treated extract was less than 1.0 CFU/mL, compared to 1.20 × 10⁴ CFU/mL in the untreated sample. HPP also maintained key physicochemical properties, reducing viscosity from 18.00 mPa.s in T1 to 12.50 mPa.s in THPPc, while preserving color stability and sweetness perception. This study shows that HPP is an effective preservation method for sugarcane extract, providing a viable alternative to thermal processing by minimizing quality degradation and ensuring microbial safety.